Keanekaragaman Zooplankton Sebagai Bioindikator Kualitas Air di Situ Sipatahunan balendah Kabupaten Bandung Jawa Barat - supriyatna, ateng ateng; Mustahiq Akbar, Rahmat Taufiq; Azizah, Andini Nurul (IAIN Ternate, 2023)
Situ Sipatahunan is a lake located in the Baleendah area, Bandung Regency, West Java, has an important function for the surrounding community, especially during the dry season, however, Sipatahunan Situ has an open water system that allows disturbance to the water conditions. To find out this, it is necessary to monitor the condition of the waters which can be done biologically ,physical and chemical conditions of the waters. Therefore the purpose of this study was to determine the diversity of zooplankton and water quality conditions based on the physical and chemical parameters of the waters. This research was conducted from March to April 2023 by taking samples at 3 stations (Inlet, Central and Outlet). The physical and chemical parameters of the waters observed were temperature, brightness, pH, DO, BOD, nitrate and phosphate. Zooplankton samples were identified at the Aquatic Ecology Laboratory, Padjadjaran University, Center for Environment & Sustainability Science (CESS). The results showed that the diversity of zooplankton in Situ Sipatahunan consisted of 26 species, 10 classes and 5 phyla. The diversity index values for each station are different, namely station 1 (H'=1.2), station 2 (H'=1.3), and station 3 (H'=0.9). Based on the physical and chemical parameters of the waters, the condition of the waters of Sipatahunan Lake is included in the slightly polluted category.Keywords: Diversity, Situ Sipatahunan, Zooplankton